54 The reliability of lactate point-of-care testing in mobile intensive care units for triaging sepsis patients?. (16th April 2018) - Léguillier, T; Jouffroy, R; Boisson, M; Boussaroque, A; Chenevier-Gobeaux, C; Chaabouni, T; Vivien, B; Nivet-Antoine, V; Beaudeux, JL
Abstract : Aim: Lactate point of care testing (POCT) could be a valuable tool in a prehospital environment for helping mobile intensive care units (MICU) to determine the level of critical care and hospital triage (emergency department [ED] or intensive care unit [ICU]) needed for sepsis patients. StatStrip Lactate Xpress is a handheld POCT lactate monitoring system which is rapid and easy to use on capillary whole blood specimens. We evaluated StatStrip Lactate to determine if the clinical performance and reliability was acceptable for use on MICU's for triaging sepsis patients. Method: We first investigated POCT analytical performance including imprecision and the limits of detection. Using samples collected from 50 identified sepsis patients admitted to the intensive care unit (ICU), we compared lactate values obtained with the device to those obtained with four central laboratory analysers: one whole blood and three plasma-based methods. Results: Results were compared by least squares regression, Bland-Altmann plot and by comparing concordance within clinically relevant lactate decision ranges. We observed a reliable analytical performance of the POCT (CVs <3.8% for repeatability and <5.0% for reproducibility) an excellent correlation between POCT and central laboratory analysers (R2: 0.96–0.98, slopes:0.83–0.90, intercepts: 0.02–0.03) and an excellent concordance of the POCT results to the central laboratory analyser results (98%–100%). Conclusion: Lactate values are comparable and transferable between POCT and central laboratory analysers indicating that StatStrip Lactate could be a valuable tool in the MICU to evaluate the severity of sepsis patients and to better manage their hospital triage. Conflict of interest: None Funding: Nova Biomedical.